Women in the Service of Nation and Army (1875–1918) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The beginnings of women's organizing in Serbia take place during the 1870s, in times of the Herzegovina Uprising. Just a decade earlier, the United Serb Youth discussed if women could be full members and what they could do to contribute to national unification. Women were proclaimed guardians of tradition and educators of youth. In the wartimes, they were expected to establish hospitals and take care of the wounded. This article is focused on women‘s organizations and their role in wars involving Serbia in the second half of the 19th and the first half of the 20th century. The article attempts to analyse how they evaluated their own engagement and contribution to the national cause during the wars.
Keywords: nation; gender; national engagement; war; women‘s organizations